KONSTRUKSI GENDER ROLE DALAM IKLAN SABUN DETERJEN DI TELEVISI - Dosen Fakultas Ekonomi UNIBA Surakarta, Eny Kustiyah, Istiqomah (MAJALAH ILMIAH GEMA, 2013)
This research aims at revealing gender role construction in laundry detergent advertisement on television. It also uncovers the role of patriarchal culture to keep its status quo. The method ofthe research is descriptive qualitative. The primary sources of data are five laundry detergent advertisements which consist of B29 Pink, Total Harum, Rinso Cair, EASY, and SURF. The present researcher employs library research and note-taking technique to collect the data. Whereas thetype of data are words, phrases, clauses, sentences and narration. Feminist theory is the theoretical framework in this research. The present researcher employs hermeneutic phenomenology approachfor deeper understanding. The outcome of the research is as follows: (1) there is gender role construction in laundry detergent advertisement found in the the structural elements of the advertisement; (2) laundry detergent advertisements are the evidences of patriarchal culture in its attempt to strengthen the status quo.Key words: gender role, patriarchal culture